SAT0051 NF-KAPPAB inducing kinase (NIK) is a key regulator of angiogenesis: Implications for the role of non-canonical NF-KAPPAB signaling in synovial inflammation. (23rd January 2014) - Noort, A.R.; van Zoest, K.P.M.; Koolwijk, P.; Tak, P.P.; Tas, S.W.
Abstract : Background: In rheumatoid arthritis (RA) synovial tissue (ST), (pathological) angiogenesis can be observed already in the earliest phase of disease, which may be critical in the switch from acute to chronic inflammation. The chemokine CXCL12, which is induced via non-canonical nuclear factor-κB (NF-κB) signaling, plays an important role in angiogenesis, lymphocyte transendothelial migration, and homing of endothelial progenitor cells. Therefore, the non-canonical NF-κB pathway, with its key mediator NF-κB inducing kinase (NIK), may play an important role in pathological angiogenesis and the perpetuation of synovial inflammation in RA. Objectives: To study the role of non-canonical NF-κB signaling in pathological angiogenesis in RA. Methods: ST was obtained via mini-arthroscopy from inflamed joints of RA patients. Expression of NIK and CXCL12 was evaluated using immunohistochemistry and immunofluorescence (IF) microscopy. NIK expression was also studied in renal cell carcinoma, breast cancer tissues and normal skin. The effects of non-canonical NF-κB signaling in endothelial cells (EC) were studied in vitro using angiogenesis/tube formation assays and siRNA mediated gene silencing. Ex vivo, the effect of non-canonical NF-κB activity on angiogenesis/microvessel outgrowth was studied by comparing WT and NIK -/- mice in the aortic ring assay. Results: NIK was highly expressed in vascular structures in RA ST. NIK positive cells were negative for the lymphatic vessel markers LYVE-1 and podoplanin, but NIK co-localized with the EC marker vWF in small vessels. IF microscopy demonstrated that NIK, p52 and CXCL12 were expressed both in high endothelial venules and in EC of small (newly formed) blood vessels. NIK was also expressed in EC in renal cell carcinoma and breast cancer tissues, whereas normal skin EC did not exhibit increased NIK expression. In vitro, EC treated with stimuli that induce non-canonical NF-κB signaling significantly enhanced tube formation 2, 5-fold (p<0.05), which could be completely blocked by siRNA targeting NIK or IKKα, but not completely by IKKβ. Aortic rings from WT and NIK -/- mice showed normal VEGF-induced microvessel outgrowth. However, whereas non-canonical stimuli such as lymphotoxin (LT) induced microvessel sprouts in WT mice, no microvessel outgrowth was observed in aortic rings from NIK -/- mice. Conclusions: NIK is preferentially expressed in small EC in RA ST and in tumor tissues. In vitro, induction of non-canonical NF-κB signaling resulted in EC activation and enhanced angiogenesis, whereas selective blockade of this pathway using siRNA abrogated these effects. Ex vivo, LT-induced microvessel outgrowth was severely impaired in aortic rings of NIK -/- mice. These findings point towards an important role of the non-canonical NF-κB pathway in pathological angiogenesis. This could be exploited for the development of future new therapies, which would not only be applicable for RA but also for other diseases such as cancer. Disclosure of Interest: None Declared